Combined influence of nonlinearity and dilation on slope stability evaluated by upper-bound limit analysis - Tang, Gao-peng; Zhao, Lian-heng; Li, Liang; Chen, Jing-yu (Journal of Central South University, 2017)
The combined influence of nonlinearity and dilation on slope stability was evaluated using the upper-bound limit analysis theorem. The mechanism of slope collapse was analyzed by dividing it into arbitrary discrete soil blocks with the nonlinear Mohr–Coulomb failure criterion and nonassociated flow rule. The multipoint tangent (multi-tangent) technique was used to analyze the slope stability by linearizing the nonlinear failure criterion. A general expression for the slope safety factor was derived based on the virtual work principle and the strength reduction technique, and the global slope safety factor can be obtained by the optimization method of nonlinear sequential quadratic programming. The results show better agreement with previous research result when the nonlinear failure criterion reduces to a linear failure criterion or the non-associated flow rule reduces to an associated flow rule, which demonstrates the rationality of the presented method. Slope safety factors calculated by the multi-tangent inclined-slices technique were smaller than those obtained by the traditional single-tangent inclined-slices technique. The results show that the multi-tangent inclined-slices technique is a safe and effective method of slope stability limit analysis. The combined effect of nonlinearity and dilation on slope stability was analyzed, and the parameter analysis indicates that nonlinearity and dilation have significant influence on the result of slope stability analysis.